Electronic Circular Dichroism Unravels Atropisomers of a Broadly Absorbing Fulgide Derivative. Issue 9 (31st May 2022) - Hermanns, Volker; Scheurer, Maximilian; Dreuw, Andreas; Wachtveitl, Josef; Braun, Markus; Heckel, Alexander
Abstract: We prepared and studied six atropisomers with different chiroptical properties emerging from a single, robust, broadly‐absorbing fulgide photoswitch. After separation of the different atropisomers via HPLC on a chiral column, their isomerization processes at room temperature and the energy barriers of the different species were investigated in detail using spectroscopic and theoretical methods. Abstract : Taking a closer look : We report the six atropisomers with different chiroptical properties emerging from a single fulgide photoswitch. We were able to separate the different atropisomers via chiral HPLC. Spectroscopic and theoretical methods were used to gain knowledge about the isomerization processes.